The impact of uncertainty and commodity prices shocks on emerging economies, - Andre Cordeiro Valerio (2016)
This work analyzes how five Latin American economies (Brazil, Chile, Colombia, Mexico and Peru) are impacted by shocks in the world economy uncertainty and in commodity price. Analysis is based on Bayesian Structural Vector Autoregressions (BSVAR) with block exogeneity. A shock that reduces global uncertainty increases commodity price. The economies react almost as similar as in the case of a pure (positive) shock to commodity price: sovereign risk falls, the exchange rate appreciates, and GDP increases. However, the inflationary impact is not necessarily the same. A pure commodity price shock generates inflation, despite the nominal exchange rate appreciation. But an increase in commodity price due to reduction in global uncertainty is not as inflationary because of the financial channel: the nominal exchange rate appreciation is more profound due to a more intense contraction in sovereign risk. Central bankers need to properly interpret the origin of oscillations in commodity price to conduct monetary policy appropriately